MENENTUKAN SUDUT ISTIMEWA TRIGONOMETRI DENGAN ATURAN LIMA JARI - Gunadi, Farid (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
Most   of   Students   in   High School are not mastering in Trigonometry subject.  It is because the learning trigonometry arithmetic is new material on the curriculum in High school level and even just a little discussed in class IX of junior high school level. Then, in learning trigonometry the students are required to memorize a lot of formulas and should be able to use the formula quickly.    The other subjects,  such  as mathematics, trigonometry material  is structured and organized as well as, trigonometry subjects should also be understood from the basic framework. The basic of trigonometry is students must be able to determine the comparative value of trigonometry appropriately. One way to facilitate the students  in  order  to  determine  easily the  value  of  a  special  angle  is  using ?the  five  finger  technique? trigonometry.  Through this technique, The writer is expected that students can easily  remember  and  memorize  the basic concept of determining the comparative value of trigonometry with special angle.